2020
DOI: 10.1177/0361198120919401
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Parking Lots for Microscale Urban Heat Island Mitigation

Abstract: Paved surfaces, especially parking lots, occupy a significant proportion of the horizontal surface area in cities. The low albedo of many of these parking lots contribute to the urban heat island (UHI) and affect the local microclimate around them. The albedo of six parking lots in Champaign-Urbana, U.S., was measured using a ground-based albedometer and was found to vary between 0.18 and 0.28, with a statistically significant variation in albedo at different points within each parking lot. The numerical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In the case of the same albedo level, the temperature will be lower in the square than in the courtyard [ 133 ]. The use of a high albedo surface in a dispersed context may improve thermal comfort at the pedestrian level [ 222 ], and alleviate UHI [ 212 , 223 ], but also lower the ambient peak temperature [ 183 , 224 ] and thus also the cooling load in buildings [ 196 , 224 ]. Research in Australia has shown that for every 10% albedo increase, the decrease in peak cooling load was about 3.5% [ 224 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the same albedo level, the temperature will be lower in the square than in the courtyard [ 133 ]. The use of a high albedo surface in a dispersed context may improve thermal comfort at the pedestrian level [ 222 ], and alleviate UHI [ 212 , 223 ], but also lower the ambient peak temperature [ 183 , 224 ] and thus also the cooling load in buildings [ 196 , 224 ]. Research in Australia has shown that for every 10% albedo increase, the decrease in peak cooling load was about 3.5% [ 224 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
“…Research in Australia has shown that for every 10% albedo increase, the decrease in peak cooling load was about 3.5% [ 224 ]. The USA example shows that increasing the parking lot albedo can lower temperatures by about 1 °C [ 223 ]. Increasing the albedo in densely built-up areas is unwise because it implies an increase in the mean radiation temperature [ 214 , 225 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
“…The use of cool materials may be effective in hot and arid climates; however, their use in cold and humid continental climates must be carefully considered, given that they may decrease the benefits of heat [ 134 , 135 , 136 ]. Even in a hot and arid climate, an increase in solar reflection due to cool pavement in urban areas can increase the heat stress of pedestrians [ 137 , 138 ]. It is cost-efficient to use cool materials; however, overall, it is more effective to rely on vegetation cover, green space, and trees to mitigate UHI effect [ 22 , 122 , 128 ].…”
Section: Control Of Outdoor Temperaturementioning
confidence: 99%
“…Parking spaces heat up during the day and contribute to a higher temperature. At night, these warm surfaces contribute to the urban heat island effect [44]. If the cars are parked on the driving lane, without additional parking places, the street segments represent a value of 2.…”
Section: Grey Parking Spacesmentioning
confidence: 99%